A comparison of head-down tilt with low-dose infusion of atrial natriuretic peptide in man. - Allen, M J (1989)
1. Procedures that increase atrial pressure, such as head-down tilt, result in an increase in plasma atrial natriuretic peptide (ANP) and a natriuresis, but a direct cause-and-effect relationship between these two responses has not been established. This study was undertaken to compare the effects of head-down tilt with exogenous ANP on renal function. 2. Eight normal sodium-replete volunteers underwent a 3 h placebo infusion, a 3 h ANP infusion at 1.2 pmol kg-1 min-1 and a 3 h period of head-down tilt. Each procedure was performed on a separate day, in random order. 3. ANP and head-down tilt produced similar increases in sodium excretion (65 +/- 24 and 68 +/- 16%, respectively). ANP did not increase urine flow significantly more than placebo. Head-down tilt increased urine flow significantly more than placebo and ANP. 4. Plasma ANP rose from 8.1 +/- 1.0 to 11.4 +/- 2.5 pg ml-1 during head-down tilt and from 6.5 +/- 1.4 to 32.3 +/- 10.7 pg ml-1 with ANP infusion. 5. ANP infusion had no significant effects on systemic haemodynamics whilst head-down tilt increased cardiac output and reduced heart rate and an index of systemic vascular resistance. 6. ANP infusion, whilst achieving a natriuretic response similar to that of tilt, was associated with a 3-fold higher mean plasma ANP level. Although plasma ANP rose during both ANP infusion and tilt, there was a lack of correlation between natriuretic response and plasma ANP. 7. The results are not compatible with a direct cause-and-effect relationship between plasma ANP and sodium excretion during head-down tilt.